Mindfulness and emotion regulation: promoting well-being during the transition to college. Issue 6 (2nd November 2018) - Finkelstein-Fox, Lucy; Park, Crystal L.; Riley, Kristen E.
ABSTRACT: Background and Objectives: Managing stress is very important for first-year college students adjusting to undergraduate life. Aspects of emotion regulation, including mindfulness and the ability to regulate distressing emotion adaptively, often correlate positively with well-being. However, little research has examined overlapping and/or distinct effects of these constructs in predicting changes in adjustment over a stressful transition. Thus, the present study examined the contributions of mindfulness and adaptive emotion regulation abilities in maintaining well-being during the transition to college. We further examined experience with mind–body practices, which may promote mindfulness and positive adjustment. Design: Online surveys were administered to 158 undergraduates near the beginning and end of their first semester. Methods: Near semester start and end, students reported levels of mindfulness, adaptive emotion regulation abilities, emotional and spiritual well-being, and experience with mind–body practices. Results: Compared to mindfulness, adaptive emotion regulation abilities largely demonstrated stronger cross-sectional and longitudinal associations with well-being. However, mindfulness uniquely protected against changes in depression for students with greater emotion regulation difficulties. Over half of participants reported having tried mind–body practices, but just 1% reported current use. Conclusions: Promoting mindfulness practices and adaptive emotion regulation abilities at the start of college may build resilience in undergraduate students.